2023
DOI: 10.1108/mf-03-2023-0149
|View full text |Cite
|
Sign up to set email alerts
|

Managerial incentives for ESG in the financial services industry: direct and indirect association between ESG and executive compensation

Jooh Lee,
Kyungyeon (Rachel) Koh,
Eunsup Daniel Shim

Abstract: PurposeThis study investigates the empirical association between environmental, social and corporate governance (ESG) performance and top executive compensation in the US financial services industry. Considering that financial firms can inflict systemic shocks across the economy, it has been argued that they must conduct ethical and sustainable business in accordance with ESG principles. This study examines whether ESG efforts are beneficial to managers.Design/methodology/approachThe authors use CEO compensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Additionally, it is emphasized that firms incorporating ESG metrics in executive compensation tend to attract a higher level of engagement and financial commitment from institutional investors, reflecting a congruence with shareholder interests. Similarly, Lee et al (2023) found that ESG performance ratings are strongly associated with all forms of compensation in US financial firms. Among the three ESG pillars, only social and governance exhibit persistent and significant associations with both short-and long-term executive pay.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 82%
“…Additionally, it is emphasized that firms incorporating ESG metrics in executive compensation tend to attract a higher level of engagement and financial commitment from institutional investors, reflecting a congruence with shareholder interests. Similarly, Lee et al (2023) found that ESG performance ratings are strongly associated with all forms of compensation in US financial firms. Among the three ESG pillars, only social and governance exhibit persistent and significant associations with both short-and long-term executive pay.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 82%
“…Executive salaries, bonuses, and other kinds of annual remuneration are significant factors in corporate governance and executive decision-making [ 51 ]. Our research shows a negative relationship between annual compensation and ESG investment; hence, we reject H8 .…”
Section: Resultsmentioning
confidence: 99%
“…The four papers accepted for the special issue analyze the relationship between corporate governance characteristics and ESG activities. Lee et al (2024) examine the link between ESG performance and top executive compensation in the USA financial services industry. The results reveal that an increase in ESG performance, and specifically social and governance performance indicators, is positively related to an increase in CEO compensation.…”
Section: Corporate Governance and Esg Activitiesmentioning
confidence: 99%
“…Rahman and Wu (2024) call for further investigation of the role of ESG performance and disclosure (and separate pillars) in M&A deals, as it has been observed that involvement in ESG activities significantly effects the relation between ESG strategy and corporate performance in the context of M&A activities. Lee et al (2024) call for further analysis of the effect of different economic conditions on the relationship between involvement in ESG activities and executive compensation schemes. Future research can also investigate whether explicit ESG incentives for CEOs serve to increase their own compensation or serve stakeholders' interests.…”
Section: Esg Financial Markets and Financial Performancementioning
confidence: 99%
See 1 more Smart Citation